Modulation of transcriptional mineralocorticoid receptor activity by casein kinase 1. Issue 1 (30th November 2021) - Ruhs, Stefanie; Griesler, Bruno; Huebschmann, Ralf; Stroedecke, Katharina; Straetz, Nicole; Ihling, Christian; Sinz, Andrea; Masch, Antonia; Schutkowski, Mike; Gekle, Michael; Grossmann, Claudia
Abstract: The mineralocorticoid receptor (MR) with its ligand aldosterone (aldo) physiologically regulates electrolyte homeostasis and blood pressure but it can also lead to pathophysiological effects in the cardiovascular system. Previous results show that posttranslational modifications (PTM) can influence MR signaling and function. Based on in silico and in vitro data, casein kinase 1 (CK1) was predicted as a candidate for MR phosphorylation. To gain a deeper mechanistic insight into MR activation, we investigated the influence of CK1 on MR function in HEK cells. Co‐immunoprecipitation experiments indicated that the MR is located in a protein–protein complex with CK1α and CK1ε. Reporter gene assays with pharmacological inhibitors and MR constructs demonstrated that especially CK1ε acts as a positive modulator of GRE activity via the C‐terminal MR domains CDEF. CK1 enhanced the binding affinity of aldosterone to the MR, facilitated nuclear translocation and DNA interaction of the MR, and led to expression changes of pathophysiologically relevant genes like Per ‐ 1 and Phlda1 . By peptide microarray and site‐directed mutagenesis experiments, we identified the highly conserved T800 as a direct CK1 phosphorylation site of the MR, which modulates the nuclear import and genomic activity of the receptor. Direct phosphorylation of the MR was unable to fully account for all of the CK1 effects on MR signaling, suggesting additional phosphorylation of MR co‐regulators. By LC/MS/MS, we identified the MR‐associated proteins NOLC1 and TCOF1 as candidates for such CK1‐regulated co‐factors. Overall, we found that CK1 acts as a co‐activator of MR GRE activity through direct and indirect phosphorylation, which accelerates cytosolic‐nuclear trafficking, facilitates nuclear accumulation and DNA binding of the MR, and increases the expression of pathologically relevant MR‐target genes.